Effect of home non-invasive ventilation on left ventricular function and quality of life in patients with heart failure and central sleep apnea syndrome (Balneo and PRM Research Journal, 2022)
Abstract: Central Sleep Apnea Syndrome (CSAS) and Cheyne-Stokes breathing are prevalent in patients with heart failure with reduced ejection fraction (HFrEF). Positive respiratory pressure therapy (PAP) associated with drug therapy of heart failure can improve quality of life, although tolerance to PAP therapy can be difficult to achieve.Materials and method :Patients for this prospective, mono-centre, cohort study were selected from patients with chronic heart failure who present at the Sleep Laboratory of the Medical Clinic of Pneumology, Oradea who underwent polysomnography. 38 HFrEF and CSAS patients were included between January 2019 to December 2021 in the study,with apnea-hypopnea index (AHI) >=15/hour of sleep. Echocardiographic hemodynamic parameters (left ventricular ejection fraction-LVEF, mitral regurgitation score), PAP compliance and quality of life using the severe respiratory failure questionnaire (SRI) at the initiation of PAP and after 3 months were included.Results:After 3 months of PAP therapy LVEF increased significantly (from 31.4% ±12.2to 38.0%±10.9, p=0.0181), AHI decreased (from 40.1±18.7 to 6.8±6.1 events/h, p